Composition and Functional Diversity of Epiphytic Bacterial and Fungal Communities on Marine Macrophytes in an Intertidal Zone - Chen, Jun; Zang, Yu; Yang, Zhibo; Qu, Tongfei; Sun, Tao; Liang, Shuo; Zhu, Meiling; Wang, Ying; Tang, Xuexi (Frontiers in Microbiology, 2022)
Marine macrophytes (seagrasses and macroalgae) and their epiphytic microorganisms play an important role in the ecological and biochemical processes of coastal oceans. However, simultaneous comparative studies on the biodiversity and functions of epiphytic bacteria and fungi associated with marine macrophytes have not been conducted. In this study, high-throughput sequencing technology was used to describe the epiphytic bacterial and fungal communities of 11 common macroalgae and 2 seagrasses from an intertidal zone of northern China and compare them with seawater communities. The results showed that Proteobacteria and Bacteroidota were the dominant bacterial phyla in marine macrophytes, whereas Ascomycota, Chytridiomycota, and Basidiomycota were the dominant fungal phyla. The alpha diversity of the bacterial and fungal communities in seagrasses was the highest of all macrophyte samples. This may have been related to their ability to recruit microorganisms from multiple sources. Host phylogeny may influence bacterial community structure, and geographical differences may influence fungal community structure. The FAPROTAX data indicated that C metabolic microbes were enriched in marine macrophytes, while the FUNGuild data indicated that undefined saprotroph, which participated in organic matter degradation, were also enriched in marine macrophytes. These findings provide a theoretical basis regarding the epiphytic microorganisms of macrophytes and may offer new insights to support the improved ecological restoration of seagrass and macroalgae beds.